Влияние длительности микродугового оксидирования на морфологию и структуру кальций-фосфатных покрытий - Казанцева, Екатерина Александровна (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
In the present study, we performed the study by scanning electron microscopy (SEM) of the effect of the micro-arc oxidation (MAO) duration on the morphology and structure of the calcium phosphate (CaP) coatings. The increase in the MAO time from 2 to 10 min led to the formation of homogeneous by thickness coatings, to the thickness growth from 28.6 jum to 50.6 jum, to an increase of the average sizes of spheres and pores in the ranges of 8.7-17.2 pm and 1.4-3.2 pm, respectively, to a decrease of the inner porosity from 33.8 to 24.3 %, and did not affect the value of the surface porosity, which was varied from 16.1 to 18.1 %.